Metastatic High-Grade Endometrial Stromal Sarcoma with BCOR Translocation to the Pleural Fluid: A Case Report. (February 2023) - Gonsalves, Catherine; Ross, Julia; Esnakula, Ashwini; Leon, Marino
Sarcomas in cytology fluids are uncommon, accounting for an estimated 3-6% of malignant effusions. High-grade endometrial stromal sarcomas are uncommon malignancies, whose true frequency is not well defined. We present a case of high-grade endometrial stromal sarcoma with a BCOR translocation metastatic to the pleural fluid. A 31-year-old female with a long-standing history of abnormal uterine bleeding underwent needle core biopsy, which showed a high-grade endometrial stromal sarcoma with a BCOR translocation. In the months following her diagnosis, the patient underwent multiple cycles of chemotherapy along with radiation therapy, but had disease progression. She then presented with bilateral pleural effusions. Cytology from the pleural effusions showed single cells and three-dimensional clusters of spindle-shaped to epithelioid cells. The cell block showed many groups of the atypical cells. The histologic and immunophenotypic features were consistent with metastatic endometrial stromal sarcoma. Ten months after initial diagnosis and two months after positive pleural fluid cytology the patient was deceased. Malignant pleural fluids with sarcoma metastases are not common. Endometrial stromal sarcomas are infrequent malignancies and those with BCOR translocations are recently described with a small number of cases reported. Pleural fluid metastasis of high-grade endometrial stromal sarcoma with BCOR translocation has not, to our knowledge, been described in the literature.